“Örnek Vakalarla” Yara Yönetimi - Taylan, Seçil; Erden, Sevilay; Kaya, Pınar; Yurtseven, Şeyma; Güngör, Serap; Tosun, Betül; Karabağ Aydın, Arzu; Cici, Aybike Merve; Deniz Doğan, Sevgi; Gezer, Derya; Barış Eren, Nadiye; Baksi, Altun; et al. (Academician Publishing Book DOI Portal, 2024)
-